ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK MATERI SISTEM PERSAMAAN LINEAR PADA SOAL KONTEKS KULINER PALEMBANG - Fitrisyah, Muhammad Aidil; Zulkardi, Zulkardi; Susanti, Ely (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to determine the mathematical representation ability of educated people in the linear buying system using Palembang culinary context questions. This research uses a type of qualitative research with a descriptive approach. The research subjects were students of class XI IPA SMA, totaling 3 people. The data collection techniques used were written tests and interviews. The questions on the written test are of the type of description questions, which consist of 2 questions using the culinary context of Palembang, where the first question uses the context of lamington cake and the second question uses the context of pempek. Data analysis is done by collecting data, reducing it, presenting it, and drawing conclusions from it. The results of the research were that there were two subjects who were able to change the given problem into the form of a mathematical model so that their mathematical representation skills emerged successfully, and one subject was unable to generate mathematical representation abilities because they had not been able to change the given problem into a mathematical model form.